PENGELOLAAN SAMPAH BERBASIS ‘‘ZERO WASTE’’ SKALA RUMAH TANGGA SECARA MANDIRI DI KOMPLEK DELTA 3 DILI TIMOR-LESTE - Mohammad Mirwan; jose Senses (EnviroUS, 2021)
Garbage can be defined as waste generated from human and animal activities in solid form, which is disposed of because it is no longer useful or needed. Dili is a capital city in Timor Leste which has a fairly large population. The large population in Dili causes a large amount of waste to be generated. This is an obstacle in waste management in the city of Dili where people are not aware of environmental cleanliness. Household-scale waste management can be done with the concept of zero waste. The principle of zero waste or zero waste is a waste management concept based on recycling activities. Waste management is carried out by sorting, composting and collecting goods worth selling. The purpose of this study is to determine waste management in Dili City and reduce waste generation with a zero waste program on a household scale independently in Delta 3 Complex, Dili City. Data collection methods were conducted by interview and field observation (primary data), as well as Dili City BPS Archives and Dili SAS Archives (secondary data). The study was conducted for 14 days at the Delta 3 Complex in Dili. Garbage is separated and set aside for paper, cardboard, organic waste, bottles or plastic containers. After sorting, the waste will be weighed according to its type and recorded every day. From the sorting that was carried out for 14 days with the community, it was found that a total of 365.1 kg of waste could be set aside for further composting of organic waste and plastic bottles and containers for recycling in the form of ecobricks by the community. The conclusion in this study is that waste management in Dili City is carried out by the Waste Office by implementing a transport and disposal system in which waste after being transported from the source of the waste is directly disposed of to the TPA and burned manually. Waste management with zero waste at the Delta 3 Dili Complex can reduce the accumulation of waste by 55.68% which before being separated from 365.1 kg to 161.8 kg.